High resolution crystal structure of deoxy hemoglobin from Trematomus bernacchii at different pH values: the role of histidine residues in modulating the strength of the root effect. - MAZZARELLA, LELIO; VERGARA, ALESSANDRO; MERLINO, ANTONELLO; L. VITAGLIANO; G. BONOMI; S. SCALA; C. VERDE; G. DI PRISCO (Proteins: Structure, Function, and Bioinformatics, 2006)
The Root effect is a widespread property in fish hemoglobins (Hbs) that produces a drastic reduction of cooperativity and oxygenbinding ability at acidic pH. Here, we report the high-resolution structure of the deoxy form of Hb isolated from the Antarctic fish Trematomus bernacchii (HbTb) crystallized at pH 6.2 and 8.4. The structure at acidic pH has been previously determined at a moderate resolution (Ito et al., J Mol Biol 1995;250:648–658). Our results provide a clear picture of the events occurring upon the pH increase from 6.2 to 8.4, observed within a practically unchanged crystal environment. In particular, at pH 8.4, the interaspartic hydrogen bond at the a1b2 interface is partially broken, suggesting a pKa close to 8.4 for Asp95a. In addition, a detailed survey of the histidine modifications, caused by the change in pH, also indicates that at least three hot regions of the molecule are modified (Eb helix, Cb-tail, CDa corner) and can be considered to be involved at various levels in the release of the Root protons. Most importantly, at the CDa corner, the break of the salt bridge Asp48a–His55a allows us to describe a detailed mechanism that transmits the modification from the CDa corner far to the a heme. More generally, the results shed light on the role played by the histidine residues in modulating the strength of the Root effect and also support the emerging idea that the structural determinants, at least for a part of the Root effect, are specific of each Hb endowed with this property